Identifications and Communicativeness as Antecedents of Citizenship Behavior of Employees of the Penitentiary Services - Sidorenkov, Andrey V.; Borokhovski, Eugene F. (Journal of police and criminal psychology, 2023)
The present study examines (a) the relationships of employees’ identifications (interpersonal, subgroup, and group) in two components (cognitive and affective) and their personal communicativeness with two dimensions of organizational citizenship behavior (OCB) and (b) the moderating role of identifications in association between personal communicativeness and the two OCB dimensions: offering quality ideas and suggestions and providing help and support. The study was carried on a sample ( N = 265) of employees of the regional department of the Federal Penitentiary Service of Russia (FPSR), whose work largely unfolds in extreme conditions. To measure the FPSR employees’ identifications in both their components, the study employed three relevant questionnaires. OCB dimensions and organizational communicativeness were measured by expert assessments of supervisors using two specially designed questionnaires. The following results were found. Subgroup identification (in its affective component only) was significantly positively associated with one OCB dimension—offering quality ideas and suggestions, as was interpersonal identification (only in its affective component though) positively associated with both OCB dimensions. Group identification (in both its components) was not associated significantly with either of the two studied OCB dimensions. Personal communicativeness was positively correlated with both dimensions of OCB, and this association was stronger than for either of the identifications. Subgroup identification moderates the relationship between personal communicativeness and the two dimensions of OCB. Conceptual and practical implications of the study results are discussed.